Gestión de las cuentas por cobrar de la Empresa POMGARBEL S.A Del Cantón Babahoyo durante el periodo 2021 -2022. - Alarcón Terranova, Anthony Armini (2023)
The study focuses on the company PONGARBEL S.A., based in Babahoyo, Ecuador, and its management of accounts to be collected in the period 2021–2022. Despite being well positioned in the wholesale market for bananas, the company faces challenges in its management of outstanding accounts. The problem lies in the lack of liquidity and unnecessary costs due to accumulated outstanding accounts. The research justifies the importance of efficient account management for the financial health of the company, the reduction of delays, and the improvement of customer relationships. The methodology is based on a descriptive and analytical approach, which includes the collection of quantitative and qualitative data as well as statistical techniques to assess credit risk and the aging of debit accounts. The results show that PONGARBEL S.A. has a robust policy of managing accounts to be charged, granting reasonable credit terms, and employing efficient collection strategies. In addition, they have implemented technology and automation in their account management process. The coverage rate for non-debitable accounts increased in 2022, indicating an improvement in management.